2018
DOI: 10.1182/blood-2017-09-805895
|View full text |Cite
|
Sign up to set email alerts
|

Pevonedistat, a first-in-class NEDD8-activating enzyme inhibitor, combined with azacitidine in patients with AML

Abstract: Pevonedistat (TAK-924/MLN4924) is a novel inhibitor of NEDD8-activating enzyme (NAE) with single-agent activity in relapsed/refractory acute myeloid leukemia (AML). We performed a phase 1b study of pevonedistat (PEV) with azacitidine (AZA) based on synergistic activity seen preclinically. Primary objectives included safety and tolerability, and secondary objectives included pharmacokinetics (PK) and disease response. Patients ≥60 years with treatment-naive AML (unfit for standard induction therapy) received PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
156
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(164 citation statements)
references
References 54 publications
8
156
0
Order By: Relevance
“…6,7 Pevonedistat treatment largely blocks cullin neddylation and inhibits cullin-RING E3 ligase activity, and in turn leads to the accumulation of tumor suppressor substrates to induce cell-cycle arrest, senescence or apoptosis in GBM cells. [8][9][10][11][12] Thus, developing a rational combination therapy with pevonedistat may improve anticancer strategy. 5 Several combinations of pevonedistat and anticancer agents have been proposed to enhance the cytotoxic effect of pevonedistat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Pevonedistat treatment largely blocks cullin neddylation and inhibits cullin-RING E3 ligase activity, and in turn leads to the accumulation of tumor suppressor substrates to induce cell-cycle arrest, senescence or apoptosis in GBM cells. [8][9][10][11][12] Thus, developing a rational combination therapy with pevonedistat may improve anticancer strategy. 5 Several combinations of pevonedistat and anticancer agents have been proposed to enhance the cytotoxic effect of pevonedistat.…”
Section: Introductionmentioning
confidence: 99%
“…5 Several combinations of pevonedistat and anticancer agents have been proposed to enhance the cytotoxic effect of pevonedistat. [8][9][10][11][12] Thus, developing a rational combination therapy with pevonedistat may improve anticancer strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Soucy et al reported potent inhibition of Uba3 in the single-digit nanomolar range with cross-reactivity against other E1s in the low micromolar range (Soucy et al, 2009). Pevonedistat is currently being tested in clinical trials of patients with acute myeloid leukemia, where the principal side effect seems to be liver toxicity and sepsis due to disruptions in the GTPase RhoA cytoskeleton protein and tumor necrosis factor (TNF)-α (Swords et al, 2017;Swords et al, 2018).…”
Section: Activity-based Small Molecule Screens For Ups Inhibitorsmentioning
confidence: 99%
“…An example of this mechanism is the NEDD8-E1 enzymei nhibitor (MLN4924;S cheme 1), which is in clinical trials for the treatment of chronic myelomonocytic leukemia anda cute myeloid leukemia. [30] Thism olecule forms ac ovalent complex with Nedd8, which has high affinity for aN EDD8-specific activating enzyme,U BA3 [31] (Figure 2). Alternatively,PPI inducers can stimulate gain-of-function behavior.O ne example of this behavior is the approved acute promyelocytic leukemia drug, arsenic tri-oxide.…”
Section: Ppi Inducersmentioning
confidence: 99%
“…The resulting modifiedprotein is apotent inhibitoro fU BA3, forming as table modified NEDD8-UBA3complex. [30,31,46] UBA3 is typically complexedtot he regulatory factor, NEDD8-activating enzymeE 1r egulatory subunit (NAE1); however,NAE1 is omitted here for clarity. ChemBioChem 2019ChemBioChem , 20,1091ChemBioChem -1104 www.chembiochem.org the BCLX L -specific inhibitor A-1331852 has been the subject of severalstudies, but has not yetreached clinicaltrials.…”
Section: Approved Ppi Blockersmentioning
confidence: 99%